Tourism Potential of Plants Species Used for the Treatment of Malaria and Typhoid Fever in Omo Forest Reserve Southwest Nigeria - Okosodo, Francis; Mohapatra, Sarada Prasad (Journal of Tourism and Hospitality Education, 2021)
This research study was carried out to investigate medicinal plant species that is used to treat malaria and typhoid fever and to provide information on the tourism potentials of these plants species in Omo forest reserve southwest Nigeria. The study area was divided into two compartments for the purpose of this research work, undisturbed forest and secondary forest compartments. Data was collected using field surveys and visiting traditional medicine homes for parts the used for the treatment of malaria and typhoid fever. Field trips were embarked upon for three months from July to September 2020 for medicinal plant species identification. The researchers were accompanied by a field assistant who can identify the plant species in local languages.. The computer PAST Model version 3 was used to analyze plant species diversity indices. The result obtained from the study shown that the study area is rich in plant species that are used to treat malaria and typhoid fever in southwest Nigeria. In all, a total of 81 plant species belonging to 42 families were recorded in the study area with great tourism potential when a sustainable management is set up. The family Asteraceae has a plant diversity of 6 and this is followed by Rubiaceae and Solanaceae family’s which have five (5) each Figure 2. The diversity index was higher in the undisturbed compartment (4.414) than the secondary forest compartment (4.364).